A review of the biochemical products produced during mammalian decomposition with the purpose of determining the post-mortem interval. Issue 4 (3rd July 2020) - Nolan, Ashley-N'Dene; Mead, Robert J.; Maker, Garth; Speers, Samuel J.
ABSTRACT: This review focuses on the biochemical products generated during the mammalian decomposition process as a means of estimating the post-mortem interval (PMI). Decomposition involves the enzymatic breakdown of the body's three main polymer-based constituents: lipids, carbohydrates and proteins. The need to identify the biochemical constituents present within decomposition fluid and the time frame of their production is crucial in understanding the decomposition process and the potential for determining the PMI. This paper provides an overview of the decomposition process, reviews recent work conducted on the analysis of decomposition fluid aimed at the estimation of the post-mortem interval, and provides a suggestion for future studies.